COVID-19 Student Stress Questionnaire: Development and Validation of a Questionnaire to Evaluate Students’ Stressors Related to the Coronavirus Pandemic Lockdown - Zurlo, Maria Clelia (Front Psychol, 2020)
Clinical observations suggest that during times of COVID-19 pandemic lockdown university students exhibit stress-related responses to fear of contagion and to limitations of personal and relational life. The study aims to describe the development and validation of the 7-item COVID-19 Student Stress Questionnaire (CSSQ), a measurement tool to assess COVID-19-related sources of stress among university students. The CSSQ was developed and validated with 514 Italian university students. Exploratory Factor Analysis (EFA) was conducted with one split-half sub-sample to investigate the underlining dimensional structure, suggesting a three-component solution, which was confirmed by the Confirmatory Factor Analysis (CFA) with the second one split-half sub-sample (CFI = 0.95; TLI = 0.95; RMSEA = 0.06). The CSSQ three subscales measure COVID-19 students’ stressors related to (1) Relationships and Academic Life (i.e., relationships with relatives, colleagues, professors, and academic studying); (2) Isolation (i.e., social isolation and couple’s relationship, intimacy and sexual life); (3) Fear of Contagion. A Global Stress score was also provided. The questionnaire revealed a satisfactory internal consistency (Cronbach’s alpha = 0.71; McDonald’s omega = 0.71). Evidence was also provided for convergent and discriminant validity. The study provided a brief, valid and reliable measure to assess perceived stress to be used for understanding the impact of the COVID-19 pandemic lockdown among university students and for developing tailored interventions fostering their wellbeing.